Student Daily Calorie Intake and Physical Activity Levels during the COVID-19 Pandemic - Baharuddin Hasan; Ipa Sari Kardi; Dewi Nurhidayah (Universitas Pendidikan Indonesia, 2023)
The level of physical activity is an indicator of being active or inactive. This study aimed to determine students’ daily calorie needs according to their physical activity levels during the Covid-19 pandemic. This research was a quantitative descriptive research with a cross-sectional design. The population of this study included 588 FIK Cenderawasih University students. For the sample, the simple random sampling technique was used. The samples of this study involved 95 students aged 19–24 years, consisting of 60 males and 35 females. The data collection employed the International Physical Activity Questionnaire (IPAQ) and anthropometric measurements to determine BMI to calculate the student’s daily calorie needs. The results of data analysis showed that the level of physical activity of students was primarily in the moderate category, 52.6%, while the rest 47.4% of students were in the high category. The findings show that the average of student needs was 3101 calories/day. In addition, there were differences in calorie needs between males and females. The average energy intake for males was 3363 calories/day, while for females was 2389 calories/day. Based on the results obtained, the higher the physical activity, the higher the calorie intake.